The Influence of Tax Knowledge and Socialization Factors on Awareness of Tax Obligations in the Micro, Small and Medium Enterprises (MSME) Sector Case study on Micro, Small and Medium Enterprises (MSMEs) in Cileungsi in 2023 - Budiwijaya, Nia Wilis; Abdillah, Abdillah; Rahmaniar, Ani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The main aim of this research is to analyze and find out whether knowledge and socialization of taxation have an effect on awareness of tax obligations in the micro, small and medium enterprise (MSME) sector in the Cileungsi area. This research uses a quantitative analysis method with a sampling technique using non-probability sampling with a voluntary sampling method. The sample obtained in this research was 102 respondents with data collection using the questionnaire method. The data analysis technique used in this research uses Structural Equation Modeling (SEM) analysis based on Partial Least Square (PLS) using the SmartPLS 4.0 analysis tool. The results of this research data show that there is an influence that supports tax knowledge on increasing tax awareness, this is shown in the path coefficient value (0.438) and p-value (0.000 < 0.05). As well as the influence that supports tax socialization on increasing tax awareness, this is shown in the path coefficient (0.383) and p-value (0.000 < 0.05).